Cooperation between reparian states on issues of utilization and protection of international watercourses with reference to activities of the Sava Commission - Preradović Gordana (Međunarodni Problemi)
The paper analyses all forms of cooperation between states, which is essential when it comes to the matters of management, utilisation and protection of international watercourses. The most common way of cooperation is the establishment and action of international river commissions. Other forms of cooperation are manifested by holding of mutual consultations and providing notifications on relevant facts and circumstances for specific watercourse as well as by joint monitoring and evaluation of the conditions and data which are relevant for the prevention of causing damages to another state. In addition to the generalized presentation and analysis of the elements and forms of cooperation between countries on the matter of use and protection of international watercourses, the aim of the paper is to analyse the practical aspects of such cooperation, too. Therefore, the paper will analyse the work of the Sava Commission as an institutional framework within which the countries that signed the Framework Agreement for the Protection of the Sava River Basin cooperate with each other.